Cyclophilin–CD147 interaction enables SARS-CoV-2 infection of human monocytes and their activation via Toll-like receptors 7 and 8 - Tajti, Gabor; Gebetsberger, Laura; Pamlitschka, Gregor; Aigner-Radakovics, Katharina; Leitner, Judith; Steinberger, Peter; Stockinger, Hannes; Ohradanova-Repic, Anna (Frontiers in Immunology, 2025)
Monocytes and macrophages, as important constituents of the innate immune system, are equipped with multiple Toll-like-receptors (TLRs) to recognize invading pathogens, such as SARS-CoV-2, and mount an antiviral response. Nevertheless, their uncontrolled activation can lead to hyperinflammation seen in severe COVID-19. Surprisingly, we observed that recombinant SARS-CoV-2 Spike (S) and Nucleocapsid (N) proteins triggered only a weak proinflammatory response in human peripheral blood monocytes. By employing THP-1 and Jurkat NF-κB::eGFP reporter cell lines expressing specific TLRs, various TLR ligands and blocking antibodies, we determined that surface TLRs, including TLR2/1, TLR2/6 and TLR4 do not play a major role in SARS-CoV-2 sensing. However, monocytes are potently activated by the replication-competent SARS-CoV-2, and the response correlates with the viral uptake that is observed only in monocytes, but not in lymphocytes. We show that monocyte activation involves two distinct steps. Firstly, SARS-CoV-2 infects monocytes in a process independent of the S protein and the prime SARS-CoV-2 receptor angiotensin-converting enzyme 2. Instead, the alternative SARS-CoV-2 receptor CD147, which is highly expressed on monocytes, recognizes its well-known interaction partners cyclophilins A and B that are incorporated into SARS-CoV-2 virions. Secondly, upon viral uptake via the cyclophilin-CD147 interaction, that can be inhibited by specific CD147 blocking antibodies or competition with recombinant human cyclophilin A and B, SARS-CoV-2 RNA is recognized by TLR7/8 in endosomes, leading to upregulation of tumor necrosis factor (TNF), interleukin (IL)-1β and IL-6, comprising the core hyperinflammatory signature. Taken together, our data reveal a novel mechanism how human monocytes sense SARS-CoV-2 and suggest that targeting the cyclophilin-CD147 axis might be beneficial to alleviate overt myeloid-driven inflammation triggered by SARS-CoV-2 infection.